CIRCULATION OF ECONOMIC ACTIVITIES IN A VILLAGE OF JORHAT DISTRICT, ASSAM - Kumar Hazarika, Hemonta (International Journal of Psychosocial Rehabilitation, 2020)
This paper is an attempt to find out the circulation of rural economic activities covering both rural and urban settings. The total households of KomarGaoni, i.e., 113, are the source of collecting primary data for the study. The study is structured on the basis of exploratory research design and uses both interview schedule and observation method. The analysis indicates that occupational sources and workplaces are the prime factors in creating a relationship between rural and urban areas as they collaborate with each other.